2017
DOI: 10.3847/2041-8213/aa9a32
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: “A Search for Electron Antineutrinos Associated with Gravitational-wave Events GW150914 and GW151226 Using KamLAND” (2016, ApJL, 829, L34)

Abstract: We present a search, using KamLAND, a kiloton-scale anti-neutrino detector, for low-energy anti-neutrino events that were coincident with the gravitational-wave (GW) events GW150914 and GW151226, and the candidate event LVT151012. We find no inverse beta-decay neutrino events within ±500 s of either GW signal. This non-detection is used to constrain the electron anti-neutrino fluence and the total integrated luminosity of the astrophysical sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The KamLAND experiment (Gando et al 2016 were found for each GW event, however these signals do not satisfy the spatial and temporal requirements.…”
Section: Experimental Searchesmentioning
confidence: 93%
See 1 more Smart Citation
“…The KamLAND experiment (Gando et al 2016 were found for each GW event, however these signals do not satisfy the spatial and temporal requirements.…”
Section: Experimental Searchesmentioning
confidence: 93%
“…Two observed GW events in 2015 were both generated by the coalescence of binary BHs into a single BH. The first event, GW150914 (Abbott et al 2016c) The KamLAND experiment (Gando et al 2016) is located under 2700 meter water equivalent (m.w.e.) of vertical rock, below Mt.…”
Section: Introductionmentioning
confidence: 99%
“…All follow up observations were negative, with the exception of [89], that suggested the possible presence of a weak transient above 50 keV, 0.4 s after the merger (see also [131], [90]). The neutrino searches with AUGER [1], ANTARES and IceCube [47], KamLAND [120], Super-Kamiokande [42] were also negative. The follow up of GW151226 included the optical observations by Pan-STARRS1…”
Section: Binary Black Hole Mergers In O1 O2mentioning
confidence: 99%